Hygiene as obligatory duty of islam to meet the rising needs from the pandemic covid-19 according to the new norm / Zainab Hisham …[et al.]. - Hisham, Zainab; Mustafa@Busu, Zanirah; Junoh, Noraini; Nik Wan, Nik Zam; Nik Din, Nik Muniyati; Muhammad Hashim, Nurhidayah; Yusoff, Zulkarnain (2022)
Attention to cleanliness is an essential foundation of faith. Every Muslim must maintain the cleanliness of the human body and requires a mandatory mode of hygiene. The Covid-19 pandemic will bring uncertainties that affect hygiene and the necessities of healthy living. Thus, the article on hygiene and beneficial living aims to assess the level of hygiene practices among the Muslim community to protect themselves from COVID-19 infection. This article aims to find out the organization of personal hygiene and healthy living that will help maintain interest in performing duties while maintaining cleanliness in daily routines, especially during the COVID pandemic among the Muslim community.